Meta-Analysis of the Effect of Different Amounts of Cow Manure, Chemical (Nitrogen), and Biological Fertilizers on Some Quantitative and Qualitative Traits of Thyme (Thymus vulgaris L.) - Havva Mahnoudi asl; Mahmoud Mokhtari; Reza Sadrabadi Haghighi; مهدی الهی ترشیزی (بوم شناسی کشاورزی)
Introduction The inadequacy of the results of a single study and the need to combine the findings by scientists has led to the development of methods that allow combining the results of many independent studies. (Anjomani, 2022). The genus Thymus from the mint family (Lamiaceae) has more than 215 species in the world, of which 18 species have been identified in Iran. The medicinal plant) Thymus vulgaris L. (is one of the most important medicinal plants in the world, which is used Abundant in the pharmaceutical and food industries, it has a special place among medicinal plants (Gigord et al., 1999). The results of the application of different amounts of N, P, and K fertilizers on the growth and yield of Thymus vulgaris L. (showed the highest stem height (37. 38 cm), the yield of fresher plants (42. 78 grams per plant) and the highest the percentage of essential oil was 0. 73% in combined NPK treatment (Sharaf Zadeh, 2011). Research has shown that the highest percentage and yield of essential oil (363. 0% and 277. 00 ml per plant) was obtained from the plants cultivated with Nitroxin biofertilizer, followed by Biophosphorus and mycorrhizal fertilizers, respectively. (Mohammad pour Vashvaee et al., 2014). Meta-analysis combines the information of studies, pays attention to the comparison between studies discovers new results from previous studies, and can introduce new fields of research or new research questions. Material and Methods To perform this meta-analysis, the method introduced by Cooper was used. This method has the following steps: searching and selecting studies (data collection), coding the characteristics of each study, extracting data suitable for meta-analysis, and analyzing the data. In this research, standardized mean difference and correlation coefficient were used. It has been used to determine the size of the Hedges effect (g) (Porasmeili, 2011). Since the intended benefit in this meta-analysis is the difference between the averages of the treatment group (experiment) and the control group (control), in the meta-analysis method for the effect sizes in this research, the standardized mean difference method and the correlation coefficient to determine the Hedges effect size value (g)) has been used (Pouresmaeily et al., 2011). The standard difference between the mean of the control treatment and the mean of the experimental treatment is called the effect size (g) Equation (3 (and (4(. It was used in performance between control and experimental treatments (Cohen, 1988).g =                                                                                                                                 (3)In this regard, M1and M2 is the average performance of experimental treatment and control treatment and , standard deviation, respectively (Cohen, 1988).                                                                                                                                                       (4) In this regard, S1 and S2 are respectively the square root of the integrated variance of two treatment groups. If there is heterogeneity between studies, the random effect model is used. I2index is one of the important indices in determining the degree of heterogeneity between studies.In general, the degree of heterogeneity in the I2index is determined in the following three ways: I2≤25% indicates low heterogeneity. 50 ≤I2≤ 75% indicates moderate heterogeneity; that is, half of the total variability among effect sizes is not due to sampling error and is due to heterogeneity between studies.and I2≥ 75% indicates high heterogeneity (Higgins & green, 2011)Among more than 60 domestic studies and 28 foreign studies. The number of 15 studies that can be meta-analyzed in different subjects: "dry weight, percentage of essential oil and yield of thyme oil" were selected 102 effect sizes were ready for meta-analysis, and the rest of the studies were excluded. All the extracted data were transferred to comprehensive meta-analysis software for meta-analysis. The results reported about each of the variables were analyzed using comprehensive meta-analysis software (CMA.Version 2) developed in the United States. Results and Discussion Among more than 60 domestic studies and 28 foreign studies, 15 meta-analysis studies with 53 effect sizes related to the effect of different amounts of cow manure (30, 60, and 90 tons per hectare) on dry weight, essential oil percentage, and thyme oil yield were selected and ready for meta-analysis, and the rest of the studies were excluded. The results obtained in individual studies mostly emphasize the significance and positive effect of animal manure (cow) on quantitative and qualitative yield, while meta-analysis results show that studies of the effect of 30 tons of cow manure per hectare with an effect size (0.502 g) for weight dry and (g=0.482) were positive and incremental for oil yield and were significant with 99% confidence (P≤0.01) for the mentioned traits. These studies were heterogeneous based on the I2 index for dry weight (I2= 79.48) and for oil yield (I2= 86.79), and after drawing a funnel plot and performing the Bag and Mazumdar test, it was observed that they were symmetrical and had no diffusion error. And the obtained results are recommendable. However, the characteristics of plant height and essential oil percentage are not significant, and more studies are needed. Studies on the effect of chemical fertilizers only on the increase in dry weight yield with the effect size (g = 0.614) have been positive and significant (p≤0.01). These studies were heterogeneous based on the I2index for dry weight (I2= 93.79) and after drawing a funnel plot and performing the Bag and Mazumdar test, their symmetry and lack of diffusion error were observed, and the obtained results are recommendable. However, the effect of nitrogen chemical fertilizer on the qualitative traits of essential oil percentage and oil yield is not significant. Contrary to the results of the research that declared the effect of chemical fertilizers and different levels of nitrogen to be significant on dry weight, percentage of essential oil, and oil yield, studies on the effect of biofertilizers respectively with the effect size (g = 0.789) on dry weight (g = 0.773) (g=0.593) had the most increasing and positive effect on oil yield and essential oil percentage, and it was significant (P≥0.01). These studies were heterogeneous and symmetrical based on the I2 index for oil yield (I2=83.34) and essential oil percentage (I2=77.71), and there was no diffusion error, and its results are recommendable. The results of other researchers have considered the use of organic and biological fertilizers to increase and improve the quantitative and qualitative traits of the thyme medicinal plant, and to recommend these types of fertilizers; they have preferred these types of fertilizers over chemical fertilizers, the traits that were not significant or their studies were not symmetrical in all treatments The subject needs to conduct studies with higher accuracy for recommendation AcknowledgementIn order to carry out this research, it is necessary to acknowledge the efforts of the honorable director of the Department of Agriculture, Islamic Azad University, Mashhad branch, and the honorable professors and advisors who helped me in the research.